1987
DOI: 10.1177/026624268700500401
|View full text |Cite
|
Sign up to set email alerts
|

Capital Structure of Growing Small Firms: A 12-Country Study on Becoming Bankable

Abstract: Rein Peterson is Magna International Professor of Entrepreneurial Studies, York University, Toronto, Canada, and is currently on sabbatical leave as a senior research fellow at the National Centre for Management Research and Development at the University of Western Ontario, Canada. Joel Shulman is Assistant Professor of Finance at Babson College, Massachusetts, USA. In this paper they examine financing problems reported in 4,400 interviews conducted in 12 countries-six developed and six developing. The data wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 16 publications
1
14
0
2
Order By: Relevance
“…Initial funding sources have been the subject of international research and are a useful focus in part because firm age has yet become a variable capable of influencing this decision (Hamilton and Fox, 1998). Peterson and Schulman (1987) provided a general model relating the financial structure of the small firm to its age (or size). Financial markets are not sufficient and do not provide adequate financial opportunities for new firms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial funding sources have been the subject of international research and are a useful focus in part because firm age has yet become a variable capable of influencing this decision (Hamilton and Fox, 1998). Peterson and Schulman (1987) provided a general model relating the financial structure of the small firm to its age (or size). Financial markets are not sufficient and do not provide adequate financial opportunities for new firms.…”
Section: Resultsmentioning
confidence: 99%
“…International comparative studies by Remmers et al (1974) and Peterson and Schulman (1987) reached different conclusions. The first of these studies found the debt/ total assets ratio to be independent of firm size.…”
Section: Small Firms and Financementioning
confidence: 95%
“…For example, family firms often have unsound financial records, asset security, and equity base, making it difficult for them difficult to obtain external finance in the venturing process. Under such circumstance, family members, guided by altruistic belief, may bring in personal equity (Peterson & Shulman, 1987) or family loans, therefore easing the firm from financial anemia (Berger & Udell, 1998;Romano, Tanewski, & Smyrnios, 2000). Moreover, if the firm is short of human resources in the venturing, family members who have not formally engaged in the firm may join in without claiming any financial compensation, therefore mitigating the business from the resource shortage pressure and salary payment burden.…”
Section: Risk Taking and Performancementioning
confidence: 99%
“…Firms can bridge short periods by means of alternative instruments like supplier credits. Indeed, supplier credits are of great importance for start-ups (Peterson and Shulman 1987). In general, the supply of bank credit seems not to be the chief problem for SMEs, as the analysis of Binks and Ennew (1997) suggests.…”
Section: Derivation Of Hypothesesmentioning
confidence: 99%